2006
DOI: 10.1128/aem.72.4.2313-2321.2006
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Analysis of Fractional Multifactorial Designs To Study Attachment Strength and Transfer of Listeria monocytogenes from Pure or Mixed Biofilms after Contact with a Solid Model Food

Abstract: The aim of this study was to establish which of seven factors influence the adhesion strength and hence bacterial transfer between biofilms containing Listeria monocytogenes (pure and two-species biofilms) and tryptone soya agar (TSA) as a solid organic surface. The two-species biofilms were made of L. monocytogenes and one of the following species of bacteria: the nonpathogenic organisms Kocuria varians, Pseudomonas fluorescens, and Staphylococcus sciuri and CCL 63, an unidentified gram-negative bacterium iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 42 publications
(60 reference statements)
3
22
0
2
Order By: Relevance
“…The constant A is affected by the initial number of attached cells, but the k value is independent of A. 24,26,31,32 The k values are listed in Table 1 and most values fall in the range of 0.2∼0.5. An ATCC strain LM_7644 (serotype 1/2c) had the highest (p<0.05) k value (0.74), while LM_S20 (serotype 1/2b) and LM_S28 (serotype 4b), samples that were isolated from catfish plants, had the lowest k values (0.22) with the highest (p<0.05) attachment strength ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The constant A is affected by the initial number of attached cells, but the k value is independent of A. 24,26,31,32 The k values are listed in Table 1 and most values fall in the range of 0.2∼0.5. An ATCC strain LM_7644 (serotype 1/2c) had the highest (p<0.05) k value (0.74), while LM_S20 (serotype 1/2b) and LM_S28 (serotype 4b), samples that were isolated from catfish plants, had the lowest k values (0.22) with the highest (p<0.05) attachment strength ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…24,26,31,32 By plotting the logarithm of the number of transferred colonies as the function of the plate succession number, a one-phase curve for all L. monocytogenes strains was obtained, and the results of two representatives (LM_S3 and LM_27) were shown in Figure 1. Regression analysis showed that the data fit with the general equation CFU=A× e −kN , where CFU is the number of colonies transferred, A is the original ordinate, N is the plate succession number, and k is the value that reflects the ease of detachment of attached bacteria from the glass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst bacterial attachment has been extensively studied [26][27][28][29], considerably less attention has been given to fungal attachment with the exception of the opportunistic pathogen Candida albicans [30,31]. 0927-7765/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Work has been published regarding listerial transfer from either processing surfaces to foods or vice versa. [1][2][3][4][5][6][7] The atomic force microscopy (AFM) was invented in 1986 8 , and since then, it has been used to image stainless steel 9-13 as well as bacterial cells. [14][15][16][17][18] To generate images using AFM, a cantilever is rastered over a surface, and the change in location of a reflected laser focused on the top of the cantilever is used to monitor the surface topography of the sample.…”
Section: Introductionmentioning
confidence: 99%